Consuming agency and desire in romance : stories of love, laughter, and empowerment - Simon, Jenni M., 1978- (Communicating gender., 2018)
This book challenges stereotypes about the romance genre, examining how modern romance production serves women in multiple ways, from escapism to sexual education, from fantasy to fun, and most importantly, as a site of production for feminist texts.